Analysis of the Effect of Binary OR Operation Property in Linear Network Coding Transmission Performance. Issue 2 (3rd March 2016) - Alabady, Salah A.; Salleh, M. F. M
ABSTRACT: In all of the works related to linear network coding (LNC), researchers use the Galois field (GF) operation property to generate the coding matrix elements. The elements of the coding matrix produced from the coefficients are randomly generated and selected from the GF( q ). In this paper, we present an analytical analysis on the effect of using the binary field (OR operation) property to generate the coding matrix elements in LNC instead of using the customary GF. The LNC with binary OR operation (LNC_OR) is simulated under various multihop wireless network conditions of coefficients and coding router for three different network topologies. Each of the three network topologies has different coefficients since different network coding router is used. Performances of the LNC with the different probability of the coefficients of coding matrix base on packet delivery ratio (PDR) are analysed. Simulation results for three different network topologies confirm that LNC_OR reduces the number of lost packets received and improves PDR performance as compared to LNC with GF (LNC_GF) operation property.